Evaluasi Program Psikoedukasi dalam Mendukung Kepercayaan Diri dan Self-Regulated Learning Siswa SMP Sekolah Rakyat 9 Bandung: Pendekatan Mixed Methods - Elsa Sri Wahyuni; Pratidina Ekanesia; Rifqi farisan Akbar (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to describe self-confidence and self-regulated learning, analyze their relationship with students' perceptions of a psychoeducational program, and explore the students' experiences at SMP Sekolah Rakyat 9 Bandung. The study employs a mixed-methods approach with an embedded design. Quantitative analysis was conducted on 46 respondents using descriptive statistics and multiple linear regression, while qualitative data were obtained through interviews and observations. The results indicate that self-confidence has a positive but non-significant relationship with perceptions of the program, whereas self-regulated learning shows a negative relationship that is also non-significant. Simultaneously, self-confidence and self-regulated learning do not provide sufficient explanatory power regarding the variation in students' perceptions of the psychoeducational program. Qualitative findings reveal changes in discipline, the courage to ask questions, the ability to seek help, and adaptation to the school environment, although some students still experience difficulties with public speaking. The study's results suggest that the evaluation of psychoeducational programs needs to consider broader psychological and contextual factors.